International Tourism Demand and Economic Growth in Malaysia - Norsiah, Kadir (2008)
Being one of the more open economic sectors scrutinised by world media, the tourism industry has emerged as an important industry in Malaysia. At present, the industry is the country's third largest foreign exchange earner. The contribution of tourism industry to the economy depends on the level of demand for tourism related activities or tourism services by foreign and domestic tourists. However, the flow of foreign tourists to a particular country is believed to be dynamically unstable due to its sensitivity to various socioeconomic, socio-political, socio-cultural, and geographical factors. This thesis has identified several socioeconomic factors that may significantly affect tourist arrival from ASEAN and non-ASEAN countries to Malaysia. In addition, this study also investigated the presence of short-run and long-run relationships between tourism demand and factors influencing tourism demand. Additionally, the causal relationship between international tourism receipts and real economic growth in Malaysia was also explored. In order to address these objectives, the study used the panel data econometric fixed-/random-effects model in determining the major factors influencing tourist arrival from ASEAN and non-ASEAN countries in Malaysia based on a sample period from 1994 to 2004. Cointegration test and error-correction model were employed in investigating the presence of short-run and long-run relationships between tourism demand and its determinants. In addition, both time-series and panel causality tests were used in determining the causal relationship between international tourism receipts and real economic growth. Results indicated that income of tourist country of origin; the relative price of tourism in Malaysia; lagged prices; the prices of tourism in complementary destinations (for Singapore and Indonesia); the prices of tourism in substitute destinations (for Thailand and the Philippines); the word-of-mouth effect; the Malaysia ... Truly Asia global campaign; and the spread of the SARS in Asia are significant in determining the demand for tourism in Malaysia. In addition, the results of cointegration test and error-correction model revealed the presence of short-run and long-run relationships between tourism demand and its determinants. Moreover, the causality test results indicated that there is a strong relationship between international tourism receipts and real economic growth, which supports the hypothesis that the tourism industry is a significant contributor to the economic growth of Malaysia. The results of the study had revealed several policy implications. Firstly, Malaysia needs to maintain its price competitiveness in order to attract more tourist arrivals. Secondly, in order to continue promoting Malaysia as a preferred tourist destination in this region, Malaysia should continue to facilitate global and regional strategic alliances and smart partnerships among governments, tourist organisations and the industries, especially with Singapore and Indonesia, which were found to be complementary destinations for Malaysia. Besides, the private sector should also be encouraged to develop innovative tourism products and services to meet the demand of different market segments as well as develop potential niche markets. Thirdly, Malaysia's image as an attractive tourist destination should be further internationalised through marketing and promotion activities. Fourthly, Malaysia should step up security patrols, particularly in remote tourist resorts, to ensure the safety of tourists. Lastly, the public sector should supplement private sector efforts and concentrate on the upgrading and maintenance of existing facilities that supports the tourism sector.